Jin Gui Shen Qi Wan, a traditional Chinese medicine, alleviated allergic airway hypersensitivity and inflammatory cell infiltration in a chronic asthma mouse model. (5th December 2018) - Kao, Shung-Te; Wang, Shulhn-Der; Lin, Chih-Che; Lin, Li-Jen
Abstract: Ethnopharmacological relevance: In Asia, Jin Gui Shen Qi Wan (JGSQW) has been used for hundreds of years to treat asthma. Aim of the study: The traditional Chinese medicine JGSQW is composed of Rehmannia glutinosa, Dioscorea opposita, Cornus officinalis, Poria cocos, Paeonia suffruticosa, Alisma orientalis, Aconitum carmichaelii and Cinnamomum cassia . However, the immunological mechanism underlying the effect of JGSQW treatment on asthma remains unclear. This study examined whether JGSQW has the potential to reduce asthma symptoms in mice with chronic asthma induced by recurrent Dermatophagoides pteronyssinus (Der p) stimulation, as well as its immunoregulatory mechanisms. Materials and methods: The airways of BALB/c mice were stimulated with Der p (i.t.) once per week (50 μL, 1 mg/mL) for 6 consecutive weeks, and the mice were fed JGSQW (1 g/kg) 30 min prior to the Der p stimulation. Three days after the last stimulation, the mice were sacrificed to evaluate the airway remodelling, infiltration of inflammatory cells, lung histological features, and total IgE in the blood. Additionally, after A549 cells were treated with JGSQW, loganin, or paeoniflorin for 30 min, 10 ng/mL IL-1β was added to stimulate the A549 cells to evaluate the effect of the medicine on the ICAM-1 gene expression after IL-1β stimulation. Results: JGSQW significantly reduced the Der p-induced infiltration of inflammatory cells into airways and decreased the total IgE and Der p-specific IgG1 in serum. Collagen assays and histopathological examinations showed that JGSQW reduced lung airway remodelling. Additionally, an electrophoretic mobility shift assay and immunohistochemical staining verified that JGSQW inhibited the NF-kB expression in airway epithelial cell nuclei. JGSQW, loganin, and paeoniflorin inhibited the ICAM-1 gene expression caused by the IL-1β stimulation of A549 cells, and loganin and paeoniflorin had the maximum inhibitory effect when mixed according to the combination of doses in JGSQW. Conclusion: These results indicated that in the chronic asthma mouse model, JGSQW inhibits the infiltration of inflammatory cells into the airways and airway remodelling and exhibits specific immunoregulatory effects. JGSQW with certain doses of loganin and paeoniflorin inhibited ICAM-1 gene expression in epithelial cells. Graphical abstract: